VLSI-SoC: Design Methodologies for SoC and SiP 16th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2008, Rhodes Island, Greece, October 13-15, 2008, Revised Selected Papers - Piguet, Christian.; Piguet, Christian.; Reis, Ricardo.; Reis, Ricardo.; Soudris, Dimitrios.; Soudris, Dimitrios. (IFIP Advances in Information and Communication Technology,, 2010)
This book contains extended and revised versions of the best papers that were p- sented during the 16th edition of the IFIP/IEEE WG10.5 International Conference on Very Large Scale Integration, a global System-on-a-Chip Design & CAD conference. The 16th conference was held at the Grand Hotel of Rhodes Island, Greece (October 13–15, 2008). Previous conferences have taken place in Edinburgh, Trondheim, V- couver, Munich, Grenoble, Tokyo, Gramado, Lisbon, Montpellier, Darmstadt, Perth, Nice and Atlanta. VLSI-SoC 2008 was the 16th in a series of international conferences sponsored by IFIP TC 10 Working Group 10.5 and IEEE CEDA that explores the state of the art and the new developments in the field of VLSI systems and their designs. The purpose of the conference was to provide a forum to exchange ideas and to present industrial and research results in the fields of VLSI/ULSI systems, embedded systems and - croelectronic design and test.